Circ_0040039 May Aggravate Intervertebral Disk Degeneration by Regulating the MiR-874-3p-ESR1 Pathway - Li, Yongjin; Wang, Xuke; Xu, Haiwei; Li, Guowang; Huo, Zhenxin; Du, Lilong; Zhang, Kaihui; Shen, Li; Li, Hao; Xu, Baoshan (Frontiers in Genetics, 2021)
The functional alteration of nucleus pulposus cells (NPC) exerts a crucial role in the occurrence and progression of intervertebral disk degeneration (IDD). Circular RNAs (circRNAs) and microRNAs (miRs) are critical regulators of NPC metabolic processes such as proliferation and apoptosis. In this study, bioinformatics tools, encompassing Gene Ontology pathway and Venn diagrams analysis, and protein–protein interaction (PPI) network construction were used to identify functional molecules related to IDD. PPI network unveiled that ESR1 was one of the most critical genes in IDD. Then, a key IDD-related circ_0040039-miR-874-3p-ESR1 interaction network was predicted and constructed. Circ_0040039 promoted miR-874-3p and repressed ESR1 expression, and miR-874-3p repressed ESR1 expression in NPC, suggesting ESR1 might be a direct target of miR-874-3p. Functionally, circ_0040039 could enhance NPC apoptosis and inhibit NPC proliferation, revealing that circ_0040039 might aggravate IDD by stabilizing miR-874-3p and further upregulating the miR-874-3p-ESR1 pathway. This signaling pathway might provide a novel therapeutic strategy and targets for the diagnosis and therapy of IDD-related diseases.